The Impact of E-Cigarettes and Tobacco Heating Systems on Health: A Review of Current Research - Plizga, Jakub; Głuszczyk, Agnieszka; Makłowicz, Aleksandra; Kopczyńska, Ewelina; Szpulak, Angelika; Frańczuk, Agata; Grzelka, Michalina; Głoskowska, Julia; Kuleta, Katarzyna; Słychan, Katarzyna (Quality in Sport, 2024)
Introduction: The growing popularity of e-cigarettes (EC) and tobacco heating systems (THS) raises concerns about their impact on the health of users and passive smokers. These products are attractive to young people due to their lack of unpleasant odor and easy availability, even though they contain addictive nicotine and harmful substances. Materialtrial and Methods of Research: China's first e-cigarette was developed in 2003. The WHO, a leading global health organization, has been actively involved in regulating the advertising and use of EC. They initially allowed the advertising of EC as a healthier cigarette alternative but later banned it due to a lack of scientific evidence. In Poland, the sale of EC to persons under 18 is prohibited, but this law needs to be better enforced. ECs heat a liquid containing nicotine, creating an aerosol with toxic substances such as acetone, glycerol, acrolein, and formaldehyde. Studies show that EC use leads to adverse health effects such as headaches, nausea, contact allergies, increased blood pressure, irregular heart rhythm, thrombosis, and cancer risk. ECs also affect oral health and the respiratory system, increasing the risk of asthma and chronic obstructive pulmonary disease (COPD). THS, introduced in 2019, heats tobacco to 300°C, producing an aerosol containing carcinogenic and toxic substances. These products negatively affect the cardiovascular and respiratory systems, increasing the number of pro-inflammatory cells in the lungs and potentially producing hepatotoxic effects. Conclusion: The increasing use of EC and THS among adolescents raises serious health concerns. These products, although perceived as less harmful, contain toxic substances and addictive nicotine. Further research is needed on their long-term effects to increase patient awareness and limit the availability of these products to minors.